THERE ARE NO PERFECT ANALYTICAL METHODS - OPTIMIZATION STUDY OF A PHARMACOPOEIA METHOD FOR CLOPIDOGREL ANALYSIS - LINCA, Ioana-Nicoleta; IMRE, Silvia; TOMUȚĂ, Ioan; TERO-VESCAN, Amelia (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Clopidogrel is a chiral compound, (+)-(S)-enantiomer has antiplatelet activity, while (-)-(R)-clopidogrel is considered an impurity of the active substance. The development of HPLC methods for optical purity analysis involves the use of expensive chiral columns and the methodologies could be different in the two well recognized compendia, European (Ph.Eur.) and United Stated (USP) Pharmacopoeias. The aim of this study was to optimise the chiral chromatographic assay of clopidogrel and its impurities from tablets taking into consideration the official pharmacopoeia provision by testing the influence of the variation of different chromatographic parameters on the relative retention times of clopidogrel and official impurities in order to achive the separation performance parameters described in USP43. HPLC-UV enantioseparation of clopidogrel was performed on a column with ovomucoid as a stationary phase chiral selector and phosphate – acetonitrile mixtures as mobile phase. The official relative retention of clopidogrel and its A and C impurities could not be achieved in this study, neither by applying a classical optimization methodology nor by using the experimental design methodology which raises the issue of reviewing the pharmacopoeia provisions. A comparative discussion between the two different approaches regarding chiral separation of clopidogrel in Ph.Eur. and USP is provided.